Comparative analyses of Linderniaceae plastomes, with implications for its phylogeny and evolution - Yan, Rongrong; Geng, Yanfei; Jia, Yuhuan; Xiang, Chunlei; Zhou, Xinxin; Hu, Guoxiong (Frontiers in Plant Science, 2023)
Linderniaceae, a taxonomically complicated family, is recently established separating from the traditionally defined Scrophulariaceae. Although previous phylogenetic studies based on a few short DNA markers have made great contributions to the taxonomy of Linderniaceae, the resolution of the phylogenetic backbone of Linderniaceae needs to be improved. High-throughput sequencing technology has become a priority to address botanical taxonomy and evolution. In this study, we newly sequenced 26 plastid genomes to evaluate their phylogenetic resolution and performed comparative analyses with five published plastomes. The plastid genome size of Linderniaceae ranged from 152,386 bp to 154,402 bp, exhibiting a typical quartile structure. These plastomes encoded 114 unique genes each, comprising 80 protein-coding genes, 30 tRNA genes, and four rRNA genes, without rearrangement or inversion. The inverted repeat regions were more conserved compared with the single-copy regions. A total of 1803 microsatellites and 1909 long sequence repeats were identified, and five hypervariable regions (petN-psbM, rps16-trnQ, rpl32-trnL, rpl32, and ycf1) were screened out. Most protein-coding genes were relatively conserved during the evolutionary process, Linderniaceae plastomes were relatively conserved during the evolutionary process, with only the ycf2 gene found under positive selection. Topologies generated from plastid genomic data showed higher resolution. Phylogenomic analyses confirmed that Linderniaceae is a distinctive lineage and revealed that the presently circumscribed Vandellia and Torenia sensu Fischer et al. (2013) are nonmonophyletic. Combining morphological and molecular evidence, we supported the newly established Yamazakia separating from Vandellia and the monotypic Picria as a separate genus. These findings 2 This is a provisional file, not the final typeset article provide further evidence to recognize the phylogenetic relationships among Linderniaceae and new insights into the evolution of the plastid genomes.